Dynamics and Shifting Meanings of Balinese Greeting Forms - Adnyana, I Ketut Suar (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This research is a descriptive and qualitative study focusing on the dynamics and transformations in the importance of Balinese greeting forms. The study examined the intricate dynamics and transformations in the significance of Balinese greeting forms. The data were garnered from Balinese greeting forms found on YouTube video, TikTok, WhatsApp discussions, Balinese songs, and interviews conducted with students from Dwijendra Junior and Senior High Schools, as well as novice lecturers from Dwijendra University. Additional data sources included observations of greeting forms utilized in public venues, such as restaurants and small markets. Interactions between diners and waiters in eateries, as well as exchanges between customers and saleswomen in convenience stores were also documented. The research revealed two categories that exemplified the evolving dynamics of Balinese greeting forms: 1) BS_KK, consisting of mbok, bli/wi/kak, and adik or dek. 2) BS_KGP, comprising ci, aku, and kamu, and 3) BS_KBL, consisting of cong, cuk, and bro/brader.